İslam’da küçüklerin hukuku (Üstruşeni’nin Ahkamu’s-Sığar örneği) - Kato, Musa Mahad (My University, 2015)
İSLAM’DA KÜÇÜKLERİN HUKUKU (ÜSTRÛŞENÎ’NİN AHKÂMU’S-SIĞÂR ÖRNEĞİ) Tezimizde üç ayrı kısım yaptık: Giriş kısminde konunun amacı, yöntem ve kaynaklar, Üstrûşenin’nın hayati ve ilmi şahsiyeti burada zikre ettik. Birinci bölümü: Fıkıh ilminde ehliyet ve küçüklük, bunun altında üç alt başlık ayrılırdık burada vücub, edâ ve ibadet ehliyeti, cenin ve çocuğun ehliyeti, hacr ve kanuni temsilcilik, küçüklük devreleri burada zikre ettik. İkinci bölümü: fıkıh ilminde küçüklerin hak ve mükellefiyetleri, burada ceninin haklar, neseb, miras ve vasiyet, ayrıca çocuğun hakları, akıka ve yeni doğan çocuğa dair hükümler, nafaka, hadane, fitre, sünnet ve çocuğun dini, küçüklerin mükellefiyetleri, nafaka, kurban, zekât ve daman bu bölümünde zikre ettik.

CHILDRENS’ JURİSPRUDENCE İN İSLAM (using examples from Ahkâmu’s-Sığâr written by Ustrûşeni). This thesis has been divided into chapters, the chapters were subdivided into studies the studies further subdivided into subdivisions as follows: Introduction: the importance of this subject, reasons of its choice, previous efforts in this course, Ustrûseni’s personality , his education life and his book Ahkâmus’sıgâr have been discussed. Chapter 1: Children’s competency in Islam which further sub divided into three studies in the first and second study general information about children’s competency has been discussed, in the third study methods of specifying children and its phases in Islam has been discussed. Chapter 2: Children’s rights and obligations has been mentioned in this chapter, under this chapter fetus’s rights to lineage, inheritance, benefiting from charitable foundations and wills, children’s right to a good name, breast feeding, maintenance (Nafaka) plus their obligations like paying zakat out of their wealth though Hanefi school of law is against this idea, compensating any damage caused by them … have been discussed under this chapter.
Keywords: Hukuk; İslam